The Impact of Translation on Modern Literary Criticism Books (Selected Models) - Saeed , Dr. Mustafa Nazar (Thi Qar Arts Journal, 2025)
Translation represts a beilliant cultural bridge that spans two shores of thought, crossed by critics and literary figures to exlore new realms of perspectives and methodologies. In this research, we highlight the impact of translation on modern literary criticism book, drawing on selected examples of works translated from various languages into Arabic, which have contributed to the formation of a new critical awareness or the reshaping of existing critical concepts. we begin by tracing the early presence of translation in modern Arabic critical discourse, then examine specific examples such as translations of works by Roland Barthes, Jacques Derrida, and Northrop Frye. We observe how these translation have influenced the development of critical concepts-not only focusing on intellectual impacts but also addressing the linguistic and stylistic effects that translation has had on the fabric of Arabic critical writing.Furthermore, we explore how some translations have presented concepts in altered or even distorted forms at times, due to the translator’s choices or the inherent challenges of translation itself. The study also discusses issues of reception and the extent to which the Arab reader can engage with translated critical texts, in light of differing cultural backgrounds and the absence of certain deeply rooted concepts in the original texts. It concludes that translation, while serving as a tool for transmitting knowledge, is in fact an active agent in its production and shaping.It has contributed to steering the course of modern Arabic criticism-at times in creative ways,and at other times in problematic ones.